2019
DOI: 10.4274/tod.galenos.2019.64326
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Osteoporosis Knowledge and the Related Factors Among Women Who Attended İskenderun Public Education Center Courses

Abstract: Amaç: Bu çalışmanın amacı osteoporoz bilgi ve öz-etkililik düzeyleri ile ilişkili faktörlerin değerlendirilmesidir. Gereç ve Yöntem: Çalışma İskenderun Halk Eğitim Merkezi kurslarına katılan 19-60 yaş grubu 419 kadın ile yürütülmüştür. Osteoporoz bilgi düzeyi ölçeği (OKT) ve Osteoporoz öz-etkililik ölçeğini (OSS) kapsayan anket yüz yüze görüşme yöntemi ile uygulanmış, vücut ağırlığı ve boy uzunluğu ölçümleri tekniklerine uygun olarak yapılmıştır. Bulgular: Toplam OKT puanları yaşı >23 yıl olanlarda ≤23 yıl ola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…In a study by Gezer and Ocak (2019), the total OKT scores of the women with bachelor's degrees (13.3±4.56) were higher than those of unschooled literate women (8.9±4.76) (p<0.05). Additionally, the OKT total, OKT-exercise, and OKT-nutrition scores of the women in the high school group were found 10.4, 5.3, and 4.8 times higher than those of the unschooled literate women, respectively [18]. The difference is probably due to the different characteristics of the study populations.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a study by Gezer and Ocak (2019), the total OKT scores of the women with bachelor's degrees (13.3±4.56) were higher than those of unschooled literate women (8.9±4.76) (p<0.05). Additionally, the OKT total, OKT-exercise, and OKT-nutrition scores of the women in the high school group were found 10.4, 5.3, and 4.8 times higher than those of the unschooled literate women, respectively [18]. The difference is probably due to the different characteristics of the study populations.…”
Section: Discussionmentioning
confidence: 76%
“…In eating habits, although most of the women (95.7%) consume dairy products, the rate of adequate consumption (≥3 servings/day) of dairy products (14.3%) was not high as expected. Most of the studies evaluating osteoporosis knowledge focus on the knowledge level and health beliefs about osteoporosis, the knowledge of the importance of calcium intake, and the importance of exercise [12][13][14][15][16][17][18][19][20]. But there are few studies evaluating the association between knowledge level and dietary habits, dairy products, and calcium-rich food consumption [26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with 419 women between the ages of 19 and 60 with different education levels, it was reported that the osteoporosis self-efficacy level was low [ 18 ]. Arslan et al found that the OSES scores of the participants were low in their study, which included 236 individuals over the age of 35, 53.4% female and 34.7% literate, who applied to the bone densitometry unit of a hospital [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ülkemizde 19-60 yaş arası farklı eğitim düzeylerine sahip 419 kadın ile yürütülen bir çalışmada osteoporoz öz-etkililikyeterlik düzeyinin düşük olduğu (OÖEYÖ toplam ortalaması=743.7) bildirmiştir (Gezer & Ocak, 2019) ile "sağlıklı yaşam biçimi davranışları" arasında pozitif yönlü bir ilişki olduğunu belirlemişlerdir (Wu & Sheng, 2019).…”
Section: Discussionunclassified